A Problematic Biomarker Trial Design. (21st July 2021) - Freidlin, Boris; Korn, Edward L
Abstract: Efficient biomarker-driven randomized clinical trials are a key tool for implementing precision oncology. A commonly used biomarker phase III design is focused on testing the treatment effect in biomarker-positive and overall study populations. This approach may result in recommending new treatments to biomarker-negative patients when these treatments have no benefit for these patients.